PENGARUH BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA PEGAWAI PADA KECAMATAN MAYANGAN KOTA PROBOLINGGO - Bambang Sugih Artanto (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2023)
Human Resources is one of the main factors in the organization even as a planner, executor as well as activator in achieving organizational goals. This research aims to analyze whether organizational culture, compensation, have a significant effect on employee performance through job satisfaction as a mediating variable. The population of this research is the employees of Mayangan District Probolinggo City as the Civil Servant with a minimum working period of 1 year. The samples taken were 55 respondents. The analysis tool used is Smart PLS 4. The results showed that organizational culture has a significant effect on job satisfaction, compensation has a significant effect on job satisfaction, organizational culture has a significant effect on employee performance, compensation has a significant effect on employee performance, job satisfaction has not a significant effect on employee performance. Furthermore, job satisfaction mediates organizational culture has not a significant effect on employee performance, job satisfaction mediates compensation has not a significant effect on employee performance.